(Where) Are Disabled Girls in Virtual Space? Representation of disability and gender in Google Images - Lee, Donna (Critical Disability Discourses, 2012)
In this paper I explore virtual space as a specific location in which representation and meaning-making take place. Virtual space is a space in which modern girls spend much of their time. It is the space in which social interactions, identity formations and re/presentation occur for many girls. This space is portable, changeable, and is touted as accessible to those with impairments (although this assertion is not uncontested, Ellis & Kent, 2011); as such it is valuable to examine if and how disabled girls are represented within this space. Virtual space is vast and in order to narrow the scope of this paper, I used the search engine Google Images to pull from virtual space a selection of images that I interrogated using a mixed methods approach to ask: Are disabled girls present in virtual space? If so, where are they in that space and how are they represented there?